Arthritis in children with LRBA deficiency – case report and literature review - Semo Oz, Rotem (Pediatr Rheumatol Online J, 2019)
BACKGROUND: Lipopolysaccharide (LPS)-responsive and beige like anchor (LRBA) deficiency is categorized as a subtype of common variable immune deficiency (CVID). A growing number of case reports and cohorts reveal a broad spectrum of clinical manifestations and variable phenotype expression, including immune dysregulation, enteropathy and recurrent infections. The association between rheumatic disease and CVID generally has been well established, arthritis has been less frequently reported and minimal data regarding its clinical features and characteristic in LRBA deficiency has been published. This case report and literature review evaluates the characteristics and features of arthritis in LRBA deficiency patients. CASE PRESENTATION AND REVIEW RESULTS: Herein, we describe a unique case of LRBA deficiency first presented with poly articular arthritis. Alongside the report, a literature review focusing on LRBA deficiency, rheumatic disease and arthritis has been conducted. We reviewed 43 publications. Among these, 7 patients were identified with arthritis. Age of first presentation was six weeks to 3 years. Male to female ratio was 4/3. Two patients were diagnosed with polyarticular Juvenile idiopathic arthritis (JIA) and three with oligoarticular JIA. Each patient was found to have different genomic mutation. The treatment was diverse and included corticosteroids, cyclosporine, methotrexate, adalidumab and abatacept. CONCLUSION: Joint involvement is variable in LRBA deficiency, hence it should always be kept in mind as a differential diagnosis for a patient with combination of juvenile arthritis and clinically atypical immune dysregulation and / or immunodeficiency.